KONTRIBUSI SUB SEKTOR PERKEBUNAN DALAM PEREKONOMIAN KABUPATEN MINAHASA UTARA - Karla ., Meray; Tommy F. Lolowang; Juliana R. Mandei (AGRI-SOSIOEKONOMI, 2021)
The purpose of this research is to see plantation sectoral contribution on North Minahasa Regency economic development. This research was conducted in July 2020. The data used in this study are secondary data. Data were obtained from North Minahasa Regency’s Central Burean of Statistics and North Minahasa Province’s Central Burean of Statistics. This research used basis of Constant Price Gross Regional Domestic Product from 2010 to 2019, land area and plantation productions of North Minahasa Regency. This study uses data analysis methods, namely location quotient analysis, shift share, and contribution analysis.  The results of the research showed that plantation sub-sector is basic sector in North Minahasa Regency and had LQ value more that 1 and be able to produce goods and services for local consumption as well as exportation. Shift share analysis showed that in year of 2010-2019 plantation sectoral didn’t have competitive advantage, but it has positif effect and a good growth rate for the economy of North Minahasa